Implementing Lean Warehousing model to increase on time and in full of an SME commercial company: a research in Perú - Calcina Flores, Angie Estefani (2023)
The commercial sector currently has high demands for fast and accurate delivery of orders; however, there is a trend of increasing customer dissatisfaction that directly impacts product returns; this is mainly related to the logistics process of warehouse management. Therefore, a model was developed using the Lean Warehousing methodology and analysis tools, including Poka Yoke, 5S, Standard Work, Multi-criteria ABC, and Kardex. The case study is about an SME footwear importer and trader in Peru. A model was developed to improve the underperformance of correct and on-time delivery orders (OTIF). The research shows the improvement of the On Time index to 80.73%, In Full to 86.46%, and OTIF to 69.80%. The proposed model was implemented through a pilot and simulated through Arena software. This research demonstrates that the application of the Lean methodology together with analysis tools is viable for the improvement of processes in the warehouse area with optimal results, so this research can contribute as a guide to lay the foun- dations for improvement in SME trading companies with similar problems in the quality of delivery of orders, which by the growth they need to improve their level of service continuously.